The effect of using different training methods on developing some of the physical and skill abilities of Ghaz Al-Shamal Club basketball players - Prof. Dr. Uday Mahmoud Zahmar; Prof. Dr. Mustafa Khorshid Ahmed (Zien Journals, 2022)
The study aimed to identify the effect of using different training methods on developing some of the physical and skill abilities of the Ghaz Al-Shamal basketball players. The study hypothesized that there are statistically significant differences between the pre-and post-tests of the two experimental groups in some of the physical and skill abilities of the Ghaz Al-Shamal Basketball Club players. The researchers used the experimental method given the suitability of this method to the nature of the research and the research problem. The research sample consisted of (24) players purposely selected and divided randomly into two experimental groups. Each group consisted of (12) players after (6) players were excluded from having conducted the pilot experiment. The first group used the circuit training method and the second used the station method. The experiment lasted (12) weeks with (3) sessions per week
Keywords: The effect; training methods; skill abilities; Ghaz Al-Shamal